Implementasi Search Engine Optimization (SEO) Pada Situs Rental-mobil-malang.com Menggunakan Metode Off Page SEO - Muhammad Ilmar Alamsyah; Djoko Pramono; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Rental-mobil-malang.com is a web that provides car rental services and tour and travel packages owned by ERC Trans. This rental-mobil-malang.com web is the place where ERC Trans offered their services for their customers. But, rental-mobil-malang.com is on page 6 of google search engine result with keyword Malang car rental. So it will be difficult for new visitors to get into the web from search engines. Then the researcher analyzes rental-mobil-malang.com using Ahrefs and Moz to get the data about rental-mobil-malang.com. And then, the researcher also analyzes the top 10 webs of Google search engine results that using Malang car rental as the keyword. Based on the result of the analysis, comparison between rental-mobil-malang.com and the top 10 webs of Google search engine results, there still lack Off Page SEO optimization in rental-mobil-malang.com. This is obtained from a low level of domain authority and page authority of rental-mobil-malang.com and a low rank of the web provided by Ahrefs and Moz. To improve web rankings of the Google search engine and the domain quality from rental-mobil-malang.com, the researcher will design and implement Off Page SEO on rental-mobil-malang.com.